2021
DOI: 10.3390/plants10010163
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Botanical Families in Medicinal Ethnobotany: A Phylogenetic Perspective

Abstract: Studies suggesting that medicinal plants are not chosen at random are becoming more common. The goal of this work is to shed light on the role of botanical families in ethnobotany, depicting in a molecular phylogenetic frame the relationships between families and medicinal uses of vascular plants in several Catalan-speaking territories. The simple quantitative analyses for ailments categories and the construction of families and disorders matrix were carried out in this study. A Bayesian approach was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 77 publications
5
22
1
2
Order By: Relevance
“…These results are in line with previous ethnofloristic studies conducted in Mediterranean areas that reported Asteraceae and Lamiaceae as being the ethnobotanically overrepresented families [6,[21][22][23][24]. These two families are well represented in our territories in terms of number of taxa (20% of Tunisian flora estimated at 2700 taxa) with 319 Asteraceae and 183 Lamiaceae [8].…”
Section: Botanical Diversity Of Used Plants By the Local Population Osupporting
confidence: 91%
See 2 more Smart Citations
“…These results are in line with previous ethnofloristic studies conducted in Mediterranean areas that reported Asteraceae and Lamiaceae as being the ethnobotanically overrepresented families [6,[21][22][23][24]. These two families are well represented in our territories in terms of number of taxa (20% of Tunisian flora estimated at 2700 taxa) with 319 Asteraceae and 183 Lamiaceae [8].…”
Section: Botanical Diversity Of Used Plants By the Local Population Osupporting
confidence: 91%
“…These two families are well represented in our territories in terms of number of taxa (20% of Tunisian flora estimated at 2700 taxa) with 319 Asteraceae and 183 Lamiaceae [8]. Together with the size of the family, the importance of Lamiaceae in local ethnobotany would be explained by its economic significance thanks to its aromatic plants, and particularly by the well-known important presence and diversity of its essential oil compounds [6]. Similarly, the abundance, among other compounds, of terpene compounds (including sesquiterpene lactones) in the Asteraceae taxa would explicate their prevalence to relieve different ailments, again considering the size and diversity within the family [6].…”
Section: Botanical Diversity Of Used Plants By the Local Population Omentioning
confidence: 99%
See 1 more Smart Citation
“…The management and utilization of biological resources is central to the history of human culture and civilization, and human communities have used resources, particularly bioresources, during all times of human evolution (Gras et al 2021). Plant resources are essential to human cultures and have been used to support wellbeing for thousands of years.…”
Section: Introductionmentioning
confidence: 99%
“…The Asteraceae family is considered one of the most important sources of species of therapeutic interest in folk medicine worldwide (Gras et al, 2021), being its ethnobotanical and ethnopharmacological relevancies extensively reported in the literature (Dolisgan et al, 2020;Jayasundera et al, 2021;Michel et al, 2020;Panda et al, 2019;Yousuf et al, 2019). Popularly known as daisy, aster, compost or sunflower family, the Asteraceae accounts for approximately 1600 genera, 23,000 species and 13 subfamilies (Kenny et al, 2014;Obón et al, 2012).…”
Section: Introductionmentioning
confidence: 99%